Pengaruh Perceived Overqualification, Role Stress Terhadap Cyberloafing yang di Mediasi oleh Emotional Exhaustion pada Karyawan Perusahaan PT Pertamina - Efysastiana Putri; Yustika Anggraini; Yeny Rahman P.L; Netania Emilisa (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
The current rapid development of the oil industry is marked by increased oil exploration throughout the world, including Indonesia. The oil industry, or what is more familiarly known as the petroleum industry, has produced various kinds of fuel oil, which is initially still in the form of crude oil and then processed to become types of oil that have characteristics and advantages. This research uses quantitative tests and hypothesis testing to test the formulated hypotheses and prove the relationship between variables. The unit of analysis used is individuals, namely people who work at PT Pertamina in Jakarta and data is obtained from each individual who provides responses as a source of individual data for conducting a study through a separate questionnaire. From the results of testing the first hypothesis it shows that Perceived Overqualification has no influence on Cyberloafing. From the results of testing the second hypothesis it shows that Role Stress has no influence on Cyberloafing. From the results of testing the third hypothesis it shows that Perceived Overqualification has no influence on Emotional Exhaustion. From the results of testing the fourth hypothesis it shows Role Stress has a positive and significant influence on Emotional Exhaustion. From the results of testing the fifth hypothesis, it shows that Emotional Exhaustion has no influence on Cyberloafing.